2021
DOI: 10.1253/circj.cj-20-0655
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Characteristics and Prognosis of Acute Myocardial Infarction With Cardiogenic Shock in Japan ― Analysis From the JROAD/JROAD-DPC Database ―

Abstract: JCS-certified teaching hospitals, revealed that the 30-day mortality of acute coronary syndrome (ACS) with cardiogenic shock was as high as 34%, which remains a challenge in emergency cardiovascular medicine. 3,4 Because comprehensive management of cardiogenic shock state as well as early reperfusion therapy is vitally important for the treatment of AMI with cardiogenic shock (i.e., Killip class IV), functionally sufficient medical facilities T he in-hospital mortality rate of acute myocardial infarction (AMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…In the present study, the 30-day mortality rate of AMI patients with CS was 36.1%, which was consistent with those in previous studies. 3–5 In addition, multivariable analysis revealed that patients with MCS were significantly associated with a high risk of 30-day mortality compared with those with IABP only. However, this result does not mean that the use of MCS deteriorates the prognosis for AMI with CS compared with IABP.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, the 30-day mortality rate of AMI patients with CS was 36.1%, which was consistent with those in previous studies. 3–5 In addition, multivariable analysis revealed that patients with MCS were significantly associated with a high risk of 30-day mortality compared with those with IABP only. However, this result does not mean that the use of MCS deteriorates the prognosis for AMI with CS compared with IABP.…”
Section: Discussionmentioning
confidence: 96%
“…The short-term prognosis of acute myocardial infarction (AMI) has been improved using optimal medical therapies such as antithrombotic therapy and early revascularization, particularly indicative of primary percutaneous coronary intervention (PCI). However, among them, 6.9–15.2% are critically ill patients with AMI complicated by cardiogenic shock (CS), 1–4 and their in-hospital mortality rate is as high as 39–45%, 3–5 which makes it the leading cause of mortality in AMI patients. In addition, accumulating evidence suggests increased trends in incidence rates of CS, 1 , 4 , 6 particularly in the older than in the younger population.…”
Section: Introductionmentioning
confidence: 99%
“…Killip class was undetermined in ≈10% of patients in the present study, which is in line with a previous study using DPC database. 10 In addition, operator volume data are not available, although it is controversial whether operator rather than hospital volume for PCI procedures is associated with in‐hospital mortality. 15 Because of the nature of observational study, the present investigation does not indicate causal relations of primary and total PCI volume, and primary/total PCI volume ratio to in‐hospital mortality after primary PCI for acute MI.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 A French registry, which included 37 848 total PCIs from 44 centers indicated an inverse relation between hospital total PCI volume and mortality for emergency PCIs. 8 On the other hand, a recent Japanese nationwide database study demonstrated that annual number of patients with acute MI at hospitals rather than annual total PCI volume was associated with better 30‐day mortality in patients with acute MI, 10 suggesting the differences in expertise and skills needed between acute MI and elective cases. Because patients with acute MI need specific medical care including immediate PCI with short door‐to‐balloon time, mechanical support, and post‐reperfusion care, higher PCI volume for elective cases may not translate into better clinical outcomes in acute MI at hospital level.…”
mentioning
confidence: 99%
“…In terms of data derived from Japanese population, there are several registries and databases including patients with AMI in Japan such as J-MINUET [25][26][27][28], PACIFIC [29], Tokyo CCU network registry [30], JAMIR [31][32][33][34][35], and JROAD [36][37][38]. CVIT has been working on the J-PCI registry [39][40][41][42], the largest database of patients who underwent PCI in Japan.…”
Section: Specific Differences Between Japan and Europementioning
confidence: 99%